Microbiome features in bronchoalveolar lavage fluid of patients with idiopathic inflammatory myopathy-related interstitial lung disease - Zhang, Liyan; Liu, Xueqing; Fan, Bijun; Chen, Jiajun; Chen, Jie; Li, Qiuhong; Wu, Xueling (Frontiers in Medicine, 2024)
Background Interstitial lung disease (ILD) is a common complication of idiopathic inflammatory myopathy (IIM), which is one of the connective tissue diseases (CTD). It can lead to poor prognosis and increased mortality. However, the distribution and role of the lower respiratory tract (LRT) microbiome in patients with IIM-ILD remains unclear. This study aimed to investigate the microbial diversity and community differences in bronchoalveolar lavage fluid (BALF) in patients with IIM-ILD. Methods From 28 June 2021 to 26 December 2023, 51 individual BALF samples were enrolled, consisting of 20 patients with IIM-ILD, 16 patients with other CTD-ILD (including 8 patients with SLE and 8 with RA) and 15 patients with CAP. The structure and function of microbiota in BALF were identified by metagenomic next-generation sequencing (mNGS). Results The community evenness of LRT microbiota within the IIM-ILD group was marginally lower compared to the other CTD-ILD and CAP groups. Nonetheless, there were no noticeable differences. The species community structure was similar among the three groups, based on the Bray-Curtis distance between the samples. At the level of genus, the IIM-ILD group displayed a considerably higher abundance of Pseudomonas and Corynebacterium in comparison to the CAP group (p < 0.01, p < 0.05). At the species level, we found that the relative abundance of Pseudomonas aeruginosa increased significantly in the IIM-ILD group compared to the CAP group (p < 0.05). Additionally, the relative abundance of Prevotella pallens was significantly higher in other CTD-ILD groups compared to that in the IIM-ILD group (p < 0.05). Of all the clinical indicators examined in the correlation analysis, ferritin level demonstrated the strongest association with LRT flora, followed by Serum interleukin-6 level (p < 0.05). Conclusion Our research has identified particular LRT microorganisms that were found to be altered in the IIM-ILD group and were significantly associated with immune function and inflammatory markers in patients. The lower respiratory tract microbiota has potential in the diagnosis and treatment of IIM-ILD.